Effects of High-intensity Robot-assisted Hand Training on Upper Limb Recovery and Muscle Activity in Individuals With Multiple Sclerosis: A Randomized, Controlled, Single-Blinded Trial - Gandolfi, Marialuisa; Valè, Nicola; Dimitrova, Eleonora Kirilova; Mazzoleni, Stefano; Battini, Elena; Benedetti, Maria Donata; Gajofatto, Alberto; Ferraro, Francesco; Castelli, Matteo; Camin, Maruo; Filippetti, Mirko; De Paoli, Carola; et al. (Frontiers in Neurology, 2018)
Background: Integration of robotics and upper limb rehabilitation in people with multiple sclerosis (PwMS) has rarely been investigated. Objective: To compare the effects of robot-assisted hand training against non-robotic hand training on upper limb activity in PwMS. To compare the training effects on hand dexterity, muscle activity, and upper limb dysfunction as measured with the International Classification of Functioning. Methods: This single-blind, randomized, controlled trial involved 44 PwMS (Expanded Disability Status Scale:1.5-8) and hand dexterity deficits. The experimental group (n=23) received robot-assisted hand training; the control group (n=21) received non-robotic hand training. Training protocols lasted for 5 weeks (50 min/session, 2 sessions/week). Before (T0), after (T1), and at 1-month follow-up (T2), a blinded rater evaluated patients using a comprehensive test battery. Primary outcome: Action Research Arm Test. Secondary outcomes: Nine Holes Peg Test; Fugl-Meyer Assessment Scale–upper extremity section; Motricity Index; Motor Activity Log; Multiple Sclerosis Quality of Life – 54; Life Habits assessment – general short form and surface electromyography. Results: There were no significant between-group differences in primary and secondary outcomes. Electromyography showed relevant changes providing evidence of increased activity in the extensor carpi at T1 and T2. Conclusion: The training effects on upper limb activity and function were comparable between the two groups. However, robot-assisted training demonstrated remarkable effects on upper limb use and muscle activity. https://clinicaltrials.gov NCT03561155